Reverse Roll Coating Flow with Non-Newtonian Fluids (Communications in Computational Physics, 2009)
In this study an incompressible flow with non-Newtonian fluids in the reverseroll coating process was investigated. Non-Newtonian behavior of the coatingfluid was accounted by using power law model with power index, n, ranging from 0.8to 1.2. Effect of roll speed ratio (V2/V1) of the panel roll to the applicator roll and gapdistance on the coating film thickness were also investigated. Numerical results werein good agreement with those of experimental data within 15%-20%. Results indicatedthat the film thickness ratios are function of power-law index, roll speed ration and ratioof roll radius to gap distance. The equations for film thickness ratio were obtainedfrom numerical results as shown below:where t1, t2 and t3 are inlet film, transferred film and leakage film thickness, respectively,n is power-law index, V1 and V2 are roll speed of applicator roll and panel roll,Rm is average radius of two rolls and H0 is gap distance. The correlations are accuratewithin 10% for 0.8≤n≤1.2, 0.5≤V2/V1≤2, and 7.7×10−5≤ H0/Rm ≤1.54×10−4.